A Case of Patent Ductus Arteriosus with Aortic Stenosis - Ahmed, Khurshed; Hoque, Harisul; Zaman, SM Mustafa; Khaled, Fakhrul Islam; Sultan, Md Ashraf Uddin; Fatema, Nilufar; Chowdhury, MSI Tipu; Bashar, Adnan (University Heart Journal, 2019)
Patent ductus arteriosus(PDA) is a congenital cardiac disorder which is not so uncommon but it becomes rare when associated with aortic stenosis. In our case clinical finding was consistent with PDA and aortic stenosis. Echocardiographic finding showed that patient also has moderate aortic regurgitation which makes this case one of the rarest. University Heart Journal Vol. 15, No. 2, Jul 2019; 86-88